Implementing a Practical, Bachelor’s-Level Design-Based Learning Course To Improve Chemistry Students’ Scientific Dissemination Skills - Debije, Michael G. (J Chem Educ, 2019)
[Image: see text] This work presents an outline for a full-quartile design-based learning laboratory-based course suitable for final year Bachelor’s students. The course has been run for 5 years in the department of Chemical Engineering and Chemistry. The course attempts to provide a complete laboratory experience for its students, including an authentic research project, experience in writing a research paper with realistic limitations of both space and time, and giving of a presentation appropriate for a scientific conference, finally culminating with a written exam, where the questions are based on the written reports and oral presentations of the other students, making the students also course “teachers”. This article will discuss both the successful aspects of the course and point out the areas that still need improvement and provides enough information as to allow the transfer of the methodology to other educational curricula.